Metal–azole fungistatic drug complexes as anti-Sporothrix spp. agents. (19th July 2018) - Gagini, Thalita; Colina-Vegas, Legna; Villarreal, Wilmer; Borba-Santos, Luana Pereira; de Souza Pereira, Caroline; Batista, Alzir Azevedo; Kneip Fleury, Marcos; de Souza, Wanderley; Rozental, Sonia; Costa, Luiz Antônio S.; Navarro, Maribel
Abstract : Metal–antifungal drug complexes were investigated against fungus causing of sporotrichosis. They were more active against fungal cells than to mammalian cells. Abstract : The new complexes [Cu(PPh3 )2 (KTZ)2 ]NO3 (1 ), [Cu(PPh3 )2 (CTZ)2 ]NO3 (2 ), [Au(KTZ)2 ]Cl (3 ), [Au(CTZ)2 ]Cl (4 ) and Pt(KTZ)2 Cl2 (5 ) were prepared by reaction of KTZ, CTZ (where CTZ: 1-[(2-chlorophenyl)-diphenylmethyl]-1 H -imidazole and KTZ: cis -1-acetyl-4-[4-[[2-(2, 4-dichlorophenyl)-2-(1 H -imidazol-1-ylmethyl)-1, 3-dioxolan-4-yl]methoxy]phenyl]piperazine) and their respective metal salts or metal complexes under mild conditions. They were characterized using NMR, UV-vis and IR spectroscopies, microanalytical analysis and mass spectrometry. Complex (5 ) was also investigated using computational methods (DFT) to evaluate the geometry configuration around the Pt(ii ) coordination sphere; the results showed that the trans complex is the most stable one. The antifungal activities of these new compounds1–5 and some of our reported metal-based azole drug derivatives such as Pt(CTZ)2 Cl2 (6 ), [Au(PPh3 )(KTZ)]PF6 (7 ) and [Au(PPh3 )(CTZ)]PF6 (8 ) were evaluated against sporotrichosis agents ( Sporothrix schenckii, Sporothrix brasiliensis and Sporothrix globosa ). Their selectivities towards fungal cells were also evaluated. Complexes [Cu(PPh3 )2 (KTZ)2 ]NO3 (1 ), [Cu(PPh3 )2 (CTZ)2 ]NO3 (2 ), [Au(PPh3 )(KTZ)]PF6 (7 ) and [Au(PPh3 )(CTZ)]PF6 (8 ) inhibited fungal growth and killed fungi at concentrations in the nanomolar range and were more active than CTZ or KTZ alone. Microscopy analysis using scanning electron microscopy showed that the complexes1, 2, 7 and8 interfered with the cell shape. All the metal–azole complexes tested were more selective for fungi than for mammalian cells and human red blood cells, revealing that they are promising molecules for the development of new antifungal compounds.